Transferability of Skills across Sectors and Heterogeneous Displacement Costs - Yi, Moises; Mueller, Steffen; Stegmaier, Jens (American Economic Review, 2017)
We use rich German administrative data to estimate new measures of skill transferability between manufacturing and other sectors. These measures capture the value of workers' human capital when applied in different sectors and are directly related to workers' displacement costs. We estimate these transferability measures using a selection correction model, which addresses workers' endogenous mobility, and a novel selection instrument based on the social network of workers. Our results indicate substantial heterogeneity in how workers can transfer their skills when they move across sectors, which implies heterogeneous displacement costs that depend on the sector to which workers reallocate.